Chemical structure, network topology, and porosity effects on the mechanical properties of Zeolitic Imidazolate Frameworks - Tan, Jin Chong (National Academy of Sciences, 2010)
The mechanical properties of seven zeolitic imidazolate frameworks (ZIFs) based on five unique network topologies have been systematically characterized by single-crystal nanoindentation studies. We demonstrate that the elastic properties of ZIF crystal structures are strongly correlated to the framework density and the underlying porosity. For the systems considered here, the elastic modulus was found to range from 3 to 10 GPa, whereas the hardness property lies between 300 MPa and 1.1 GPa. Notably, these properties are superior to those of other metal–organic frameworks (MOFs), such as MOF-5. In substituted imidazolate frameworks, our results show that their mechanical properties are mainly governed by the rigidity and bulkiness of the substituted organic linkages. The framework topology and the intricate pore morphology can also influence the degree of mechanical anisotropy. Our findings present the previously undescribed structure-mechanical property relationships pertaining to hybrid open frameworks that are important for the design and application of new MOF materials.